ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PENGELOLAAN PERSEDIAAN BERDASARKAN COSO PADA CV. KOMBOS TENDEAN MANADO - Makikui, Lisa Elisabet; Morasa, Jenny; Pinatik, Sherly (Universitas Sam Ratulangi, 2017)
Inventory is a very important component in the operational activities of service companies engaged in the workshop. Internal control system is a process in ensuring the operational activities of the company running effectively and efficiently. COSO has 5 components in the control system that is the control environment, risk assessment, control activities, information and communication and supervision of existing performance in the company. The purpose of this research is to know the internal control system of COSO inventory management. The research method used is descriptive qualitative method and this research data obtained through interview and literature study. This research was conducted on CV. Kombos Tendean which is one of the service companies. The result of research stated that the internal control system on the management of inventory based on COSO seen from the company's operational activity has some strength because it has applied the internal control elements according to the company's SOPKeywords: COSO Internal Control SystemÂ Â